Lucid Dreaming: Intensity, But Not Frequency, Is Inversely Related to Psychopathology - Aviram, Liat; Soffer-Dudek, Nirit (Frontiers in Psychology, 2018)
Lucid Dreaming (LD) is awareness that one is dreaming, during the dream state. However, some define and assess LD relying also on controlling dream events, although control is present only in a subset of lucid dreams. LD has been claimed to represent well-being, and has even been used as a therapeutic agent. Conversely, LD is associated with mixed sleep-wake states, which are related to bizarre cognitions, stress, and psychopathology, and have been construed as arousal permeating and disrupting sleep. We propose that previous conflicting findings regarding relations between LD and both psychopathology and well-being, stem from the non-differentiated assessment of frequency and control. The present study aimed to develop an expansive measure of several LD characteristics (the Frequency and Intensity Lucid Dream questionnaire; FILD), and explore their relations with symptomatology. Undergraduate students (N = 187) self-reported trait LD, psychopathology (depression, anxiety, obsessive-compulsive symptoms, dissociation, and schizotypy), stress, and sleep problems; Two months later, a subsample (n = 78) reported psychopathology again, and also completed a dream diary each morning for 14 days. Preliminary evidence supports the reliability and validity of the FILD. Items converged into four domains: frequency, intensity (e.g., control, activity, certainty of dreaming), emotional valence, and the use of induction techniques. We report an optimal frequency cutoff score to identify those likely to experience LD within a two-week period. Whereas LD frequency was unrelated to psychopathology, LD intensity, and positive LD emotions, were inversely associated with several psychopathological symptoms. Use of deliberate induction techniques was positively associated with psychopathology and sleep problems. Additionally, we demonstrated directionality by employing a prospective-longitudinal design, showing that deliberate LD induction predicted an increase in dissociation and schizotypy symptoms across two months. We conclude that lucidity should not be considered as necessarily suggestive of well-being; LD may be positive or negative, depending on lucidity characteristics. Additionally, deliberate LD induction may harbor negative long-term risk.